ショウワキチ ノ ジシン モニタリング カンソク システム ノ コウシン ト データ リヨウ - 金尾, 政紀; カナオ, マサキ; 神沼, 克伊; カミヌマ, カツタダ; 渋谷, 和雄; シブヤ, カズオ; 野木, 義史; ノギ, ヨシフミ; 根岸, 弘明; ネギシ, ヒロアキ; 東野, 陽子; トウノ, ヨウコ; et al. (1999)
P(論文) 1997年度(第38次日本南極地域観測隊;以下JARE-38と略す)を中心に, これまで定常観測で行われてきた地震観測システムが, ハード及びソフト両面共に大幅に更新された。特に, 建造以来25年以上が経過し, 施設の老朽化が指摘されていた旧地震感震器室を閉じ, 器材をすべて撤収した。そして1996年度(JARE-37)に建設した新地震計室へ, 短周期(HES)及び広帯域(STS-1)地震計を移設あるいは新しく設置すると共に, 地学棟にワークステーションによる波形データ収録装置を新たに導入して, パソコンにより収録する旧システムから切り替えた。この地震計室及び収録装置すべてを含めての新システム導入により, 昭和基地では越冬中の地震計室見回りの労力が半減し, 基地LANを利用してのデータ収集が合理化されたため, これまでの保守作業がかなりの部分で軽減された。今後はインマルサット回線をさらに利用して, 基地外へのデータ公開の迅速化をめざす。さらに常時IP接続が可能になれば, 国内での験震処理が可能となり, 現地での完全自動化が期待される。JARE-38越冬中の経過を中心にシステム更新の詳細を記載すると共に, インターネット利用を含めたデータ公開についても簡単に述べる。 The seismic observation system at Syowa Station, East Antarctica was fully replaced in the wintering season of the 38th Japanese Antarctic Research Expedition (JARE-38) in 1996-1998. The old seismographic vault constructed in 1970 was closed at the end of JARE-38 because of cumulative damage to the inner side of the vault by continuous flowing in of water from walls in summer and its freezing in winter. All the seismometers were moved to a new seismographic hut (69°00′24.0″S, 39°35′06.0″E and 20m above mean sea level) in April 1997. Seismic signals of the short-period (HES) and broadband (STS-1) seismometers in the new hut are transmitted to the Earth Science Laboratory (ESL) via analog cable 600m in length. The new acquisition system was installed in the ESL with 6-channel 24-bit A/D converters for both sensor signals. All digitized data are automatically transmitted from the A/D converter to a workstation via TCP/IP protocol. After parallel observations with the old acquisition system by personal computers and the new system during the wintering season of JARE-38,the main system was changed to the new one, which has some advantages for both the reduction of daily maintenance efforts and the data transport/communication processes via Internet by use of LAN at the station. In this report, details of the new seismographic hut and the recording system are described. Additionally, the seismic data accessibility for public use, including Internet service, is described. ...